Análise estática e dinâmica de vigas laminadas pelo Método dos Elementos de Contorno - Nascimento Júnior, Paulo Cavalcante do (2013)
The laminated composite beams are structural components which have aroused great interest in mechanical industry due to providing components of high strength-to-weight ratio, which make them particularly suitable to the automotive and aerospace industry. In recent decades the solutions of mathematical models for laminated beam have been established in a analytical or numerical forms. The latter have been built based on finite element method (FEM) philosophy. In this work a new solution based on Boundary Element Method (BEM) for both classical and for first order laminated beam theory for static loading is established. In addition, the BEM solution is extended to deal with harmonic loading under classic beams theory hypothesis. Discussions on mathematical steps to write down both integral equations and fundamental solutions for laminated beam problem are properly made. From the formulations here proposed, codes are implemented in C++, providing displacements and efforts at the boundary and domain of the beam. In addition, numerical results for typical cases are presented as well.